(untitled) (Educational Dimension, 2021)
Reforms in education today are due to many factors, including globalization, the transition to a digital economy and citizenship, the formation of a knowledge society. That is why human digital competencies are becoming increasingly important in the development of education and affect the quality of life of every person. Modern teachers must not only possess his professional knowledge and skills but must also be able to learn throughout life. And in this context, their digital competencies play a crucial role. An important role in clarifying the state of possession of strong digital skills of teachers is played by the need for distance learning, which took place during the COVID-19 pandemic around the world, as well as in Ukraine. In order to clarify the level of digital competence of teachers in Ukraine, the Comparative Studies Department for Information and Education Innovations of the Institute of Information Technologies and Learning Tools of the National Academy of Educational Sciences of Ukraine conducted an all-Ukrainian online survey in January 2021. 1463 educators took part in the online survey, they answered five blocks of questions about their competence in the use of digital tools and instruments for distance learning and self-education: information and digital literacy, communication and cooperation, digital content creation, security and problem solving. The purpose of the article is to present the survey results and provide proposals regarding the development of teachers’ digital competence and professional development.